Putting the Green Back in Greenbacks : Opportunities for a Truly Green Stimulus - Taheripour, Farzad (World Bank, Washington, DC, 2021)
Can countries reorient their productive capacity to become more environmentally friendly and inclusive? To investigate this question, this paper uses a standard input-output modeling framework and data from 141 countries and regions to construct a new global data set of employment, value-added, greenhouse gas emissions (disaggregated into carbon dioxide and non-carbon dioxide elements), and air pollution (including nine categories of air pollutants such as fine particulate matter multipliers from supply-side investments. The analysis finds that many of the traditional sectors in agriculture and industry have large employment multipliers, but also generate male dominant, lower skill employment, and tend to have higher emissions multipliers. It is in economies dominated by these sectors that trade-offs to a “greener” transition will emerge most sharply. However, the analysis finds substantial heterogeneity in outcomes, so even in these economies, there exist other sectors with high employment multipliers and low emissions, including sectors that are more conducive to female employment. In addition, the analysis finds a high correlation between industries that generate greenhouse gas emissions, which cause long-term climate impacts, and those that generate air pollution, which have immediate harmful impacts on human health, suggesting that policies could be designed to confer longer climate benefits simultaneously with immediate health improvements. The results confirm some of the findings from recent research and shed new light on opportunities for greening economies.